A comparison of enameloplasty sealant technique and conventional sealant technique: An in-vivo study - Balaprasannakumar (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of the study is to compare two different methods: Enameloplasty sealant technique (EST) and conventional sealant technique (CST) in terms of the presence or loss of sealant and the presence or absence of caries after 6, 12, and 18 months. Materials and Methods: A total of 15 children in the age group of 7-9 years participated in the study. After taking consent, status of occlusal surface was evaluated under standardized conditions. Only mandibular molars were used in the study. On each patient, one side molar was sealed using EST and other side molar was sealed using CST. All children were recalled and examined after 6 months, 12 months and 18 months. Results: At the end of 18 months, no teeth were found carious in EST and CST group. At the end of 6, 12, 18 months there was no loss of sealants in both EST and CST group. There was no difference between EST and CST success rates. Conclusion: In our study both EST and CST showed good results. So we can do EST in deep I-Type and K-Type pit and fissures.